Public Awareness Survey on Waste Segregation in Selected Areas of Silang, Cavite: Insights from Mixed-Methods Research in Five Barangays - Reyes, Carmela; Mercado, Edna (12th International Scholars Conference 2025, 2026)
This study, Public Awareness Survey on Waste Segregation in Selected Areas of Silang, Cavite, used a mixed-methods approach, combining a descriptive survey of 200 respondents and Focus Group Discussions (FGDs), to assess public awareness, attitudes, satisfaction with services, and willingness to contribute to waste management. The growing global waste problem and the implementation of Republic Act (RA) 9003 in the Philippines reveal the urgent need for effective waste segregation and community involvement. Findings show that residents have a strong general understanding of waste segregation and its environmental impact, though awareness of RA 9003’s specific provisions remain limited. While most respondents are satisfied with current waste collection services, concerns persist regarding inadequate infrastructure, inconsistent implementation, and limited access to information. The selected barangays demonstrate a positive attitude and strong willingness to engage in waste-related activities such as segregation, composting, and clean-up drives. A majority are open to paying for improved services but due to financial constraints and concerns about transparency affect the amount they are willing to contribute. Preferred payment methods include barangay-level collection, and most respondents favor the local government as the waste service provider. Common issues such as clogged drainage, foul odors, and health risks due to improper waste disposal emphasize the critical need for more robust waste management systems. Overall, the study shows where public understanding of waste management meets real-life challenges, emphasizing the need for stronger education, better infrastructure, and consistent local leadership to make sustainable practices work effectively in communities.